Work-related psychosocial risk and “burnout” in academic personnel of some latin american countries - Botero Alvarez, Carla Cristina (Cuadernos de Administración, 2012)
Current changes in the labor market and specially those given in the universities have manifested new psychosocial-type risks that impact the physical health and mental health of the academic staff in these schools, deriving into the known “burnout syndrome”. We identified some intra-labor psychosocial risk factors that provide the development and the prevalence of “burnout syndrome” in these professionals from some Latin American countries like: Colombia, Venezuela, Argentina, and Mexico. It was concluded that certain specific aspects of the organization of work and its implementation such as: multiplicity of tasks, labor overburden, inadequate spaces, lack of time, and adequate remuneration to compensate efforts are some of the principal psychosocial risks that contribute to the later development and prevalence of the syndrome in this population.